2013
DOI: 10.1016/j.ejcb.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of myosin phosphorylation in anaphase chromosome movement

Abstract: This work deals with the role of myosin phosphorylation in anaphase chromosome movement. Y27632 and ML7 block two different pathways for phosphorylation of the myosin regulatory light chain (MRLC). Both stopped or slowed chromosome movement when added to anaphase crane-fly spermatocytes. To confirm that the effects of the pharmacological agents were on the presumed targets, we studied cells stained with antibodies against mono- or bi-phosphorylated myosin. For all chromosomes whose movements were affected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In cells treated with CalA, on the other hand, both those in which the autosomes moved backwards and those in which they did not, both sex chromosomes moved erratically up and back along the spindle axis starting in mid-anaphase, continuing throughout anaphase (Fabian et al, 2007a ; Kite and Forer, 2020 ). CalA also caused autosome poleward movements to speed up (Fabian et al, 2007a ; Sheykhani et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In cells treated with CalA, on the other hand, both those in which the autosomes moved backwards and those in which they did not, both sex chromosomes moved erratically up and back along the spindle axis starting in mid-anaphase, continuing throughout anaphase (Fabian et al, 2007a ; Kite and Forer, 2020 ). CalA also caused autosome poleward movements to speed up (Fabian et al, 2007a ; Sheykhani et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another, chromator , is implicated in spindle function in that chromosome movement was perturbed after either depletion of chromator by RNAi or by direct mutation of the chromator gene (Rath et al, 2004 ; Ding et al, 2009 ). Myosin and actin involvement in force production, and perhaps association with the spindle matrix (Johansen et al, 2011 ), is indicated by a variety of experiments including both pharmacological and molecular genetic approaches (discussed in Pickett-Heaps and Forer, 2009 ; Sheykhani et al, 2013 ; Mogessie and Schuh, 2017 ). It still is not clear what the spindle matrix is composed of, how it acts, and how actin and myosin might interact with chromator or other matrix components (e.g., Johansen et al, 2011 ), so it is difficult to know how the forces from the spindle matrix are produced.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for producing force in the absence of microtubules is actin and myosin. Actin and myosin have been identified as being present in large numbers of spindles (Forer et al 2003, Table 1) and physiological data support actin and myosin being involved in spindle function (e.g., Mogessie and Schuh, 2017;Sheykhani et al 2013aSheykhani et al , 2013b. Another possibility is the 'spindle matrix' (e.g., Johansen and Johansen, 2007;Pickett-Heaps and Forer, 2009).…”
Section: Chromosome Movement After Addition Of Noc or Colcemidmentioning
confidence: 93%
“…Consideration of actin-myosin and spindle matrix are not mutually exclusive since, as discussed in detail in Johansen et al (2011), the spindle matrix includes proteins such as the nuclear derived proteins Skeletor, Megator, Chromator and EAST and muscle proteins such as actin, myosin, and titin, that colocalize or align with the microtubule spindle in a variety of different cells types (Johansen and Johansen, 2007;Johansen et al 2011). In crane-fly spermatocytes, for example, actin, phosphorylated myosin, and titin are aligned along kinetochore microtubules (Fabian et al, 2007;Sheykhani et al 2013b), in close proximity to spindle matrix proteins (Fabian et al 2007). Just as the spindle matrix 'framework' of a spindle shape remains after removal of spindle microtubules (Johansen and Johansen, 2007;Yao et al 2012), and slowly disappears, the actin 'spindle' that remains after microtubules in mouse meiotic spindles are depolymerised with NOC also seems to slowly disappear (Mogessi and Schuh, 2017, Figure S2B).…”
Section: Chromosome Movement After Addition Of Noc or Colcemidmentioning
confidence: 99%